Effect of cation structure on the oxygen solubility and diffusivity in a range of bis(trifluoromethyl)sulfonylimide anion based ionic liquids for lithium–air battery electrolytes. Issue 16 (7th April 2016) - Neale, Alex R.; Li, Peilin; Jacquemin, Johan; Goodrich, Peter; Ball, Sarah C.; Compton, Richard G.; Hardacre, Christopher
Abstract : Electrochemical measurements of oxygen mobility and solubility in a series of related [TFSI] − -based ILs relating to cation structure and physical properties of the ILs. Abstract : This paper reports on the solubility and diffusivity of dissolved oxygen in a series of ionic liquids (ILs) based on the bis(trifluoromethyl)sulfonylimide anion with a range of related alkyl and ether functionalised cyclic alkylammonium cations. Cyclic voltammetry has been used to observe the reduction of oxygen in ILs at a microdisk electrode and chronoamperometric measurements have then been applied to simultaneously determine both the concentration and the diffusion coefficient of oxygen in different ILs. The viscosity of the ILs and the calculated molar volume and free volume are also reported. It is found that, within this class of ILs, the oxygen diffusivity generally increases with decreasing viscosity of the neat IL. An inverse relationship between oxygen solubility and IL free volume is reported for the two IL families implying that oxygen is not simply occupying the available empty space. In addition, it is reported that the introduction of an ether-group into the IL cation structure promotes the diffusivity of dissolved oxygen but reduces the solubility of the gas.